PENGAWASAN FUNGSI PERIZINAN OLEH DINAS PENATAAN RUANG KOTA BANDUNG DALAM PEMBANGUNAN APARTMENT THE MAJ COLLECTION - Nia Karniawati; Fanisa Nurfazriah (Governance, 2024)
The purpose of this study is to find out how far the licensing function is in the use of space in the city of Bandung in the construction of Apartment The Maj Collectin which is located in the Dago area. This study uses a qualitative descriptive method, using a literature study. The results of this study, the licensing function in the city of Bandung is not yet optimal, seen from the case of the construction of Apartment The Maj Collection. The conclusion of this study shows that the licensing function for spatial planning in the city of Bandung is still far from what was expected and the local government has not realized the awareness of all government officials. As a result, there has been a change in land use in the area which will have an impact on environmental damage and natural disasters such as landslides and floods.